Effect of a misting system and rooting media of Labisia pumila cuttings - Zahari, Rozihawati; Ab Shukor, Nor Aini; Abdullah, Norhayati (Asian Society of Pharmacognosy, 2018)
Labisia pumila is one of the most popular and potent ingredients used in Malay traditional herbal. However, logging activities and forest encroachment reduced the productivity of L. pumila in natural stands. In addition, the species is slow growth and its scarcity of wildings in natural forests. Due to the problems, a study on L. pumila cuttings to examine the possibility of raising planting stocks was studied. The experiment was done at FRIM's nursery with a Split-Split Plot (SSPD) in a Randomized Complete Block Design (RCBD) involving two propagation systems (misting and nonmisting), three rooting media (river sand, sawdust and 1:1 mixture of river sand and sawdust) and three plant parts (stem, petiole and leaf). Results indicated significant differences (p ≤ 0.05) in all treatments with regards to their root and shoot development. Cuttings propagated in misting system produced better rooting ability (84%) than the non-mist system (72%). However, cuttings propagated in non-mist system showed better shoot growth (29%) than the ones raised in the misting system (20%). Cuttings grown in river sand produced higher root and shoot abilities (87% and 26%) than those raised on river sand and sawdust mix (1:1) (76% and 24%) and in sawdust (72% and 23%). Stem cuttings performed best compared to leaf and petiole cuttings. In conclusion, L. pumila var. alata stem cuttings could be possibly propagated vegetatively through rooting of cuttings with favorable treatments such those raised on river sand medium under the misting propagation system.